2019
DOI: 10.1021/acsami.8b21088
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Driven Precise Control of Biological Droplet’s Adhesion on a Slippery Surface

Abstract: Precise control of a biological droplet's adhesive force on a liquid-repellent surface for smart antifouling systems is critical and fundamental to scientific research and industrial applications. Although slippery surfaces with stimuli-responsive wetting behaviors have been reported, challenge still remains in designing responsive biological droplets to achieve controllable adhesion and antifouling property. Here, we developed a thermoresponsive biological droplet adhesion system to precisely control its adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 49 publications
(77 reference statements)
0
46
0
Order By: Relevance
“…Wang et al found chain configuration of the single-stranded DNA (ssDNA) can reversibly deform in response to the temperature [67]. This chain deformation has an impact on the exposure of hydrophobic moieties on the ssDNA chain, which strongly affects the interfacial hydrophobic interaction with the lubricant.…”
Section: By Other Meansmentioning
confidence: 99%
“…Wang et al found chain configuration of the single-stranded DNA (ssDNA) can reversibly deform in response to the temperature [67]. This chain deformation has an impact on the exposure of hydrophobic moieties on the ssDNA chain, which strongly affects the interfacial hydrophobic interaction with the lubricant.…”
Section: By Other Meansmentioning
confidence: 99%
“…As a result, the motion behavior of RCA droplet changed from pinning to sliding on a tilted LIS. Reproduced with permission . Copyright 2019, American Chemical Society.…”
Section: Design and Fabrication Of E‐lismentioning
confidence: 99%
“…In our experiment, through analyzing the critical SA response to the various ATP concentrations, the detection limit of ATP could realize 5 × 10 −3 m. Based on this research, more recently, our group demonstrated that RCA biological droplet containing ssDNA displayed thermoresponsive wettability on LIS. [80] The ssDNA experienced reversible molecular configuration deformation when environmental temperature changed from 10 to 30 °C, leading to the reduced exposed hydrophobic moieties and weak interfacial adhesion. As a result, the biological droplet slid easily at higher temperature, as shown in Figure 7d.…”
Section: Fabrication Of Temperature E-lismentioning
confidence: 99%
“…(C) Magnetic field responsive SLIS (Huang et al, 2017), Copyright 2017, WILEY-VCH Verlag GmbH & Co. KGaA. (D) Temperature responsive SLIS (Wang et al, 2019). Copyright 2019, ACS.…”
Section: External Stimuli Responsive Slismentioning
confidence: 99%
“…Their biosensing applications for ATP, microRNA, and thrombin detection are also demonstrated. Based on this research, very recently, we (Wang et al, 2019) put forward a temperature responsive interfacial adhesion on SLIS. When environmental temperature increased, ssDNA became more flexible and more mobile.…”
Section: External Stimuli Responsive Slismentioning
confidence: 99%